Prevalence of BRCA1 and BRCA2 Mutations in Patients with Primary Ovarian Cancer – Does the German Checklist for Detecting the Risk of Hereditary Breast and Ovarian Cancer Adequately Depict the Need for Consultation? - Ataseven, Beyhan; Tripon, Denise; Rhiem, Kerstin; Harter, Philipp; Schneider, Stephanie; Heitz, Florian; Baert, Thais; Traut, Alexander; Pauly, Nina; Ehmann, Sarah; Plett, Helmut; Schmutzler, Rita K.; du Bois, Andreas (Geburtshilfe und Frauenheilkunde, 2020)
BackgroundBRCA1/2 mutations are the leading cause of hereditary epithelial ovarian cancer (EOC). The German Consortium for Hereditary Breast and Ovarian Cancer has defined inclusion criteria, which are retrievable as a checklist and facilitate genetic counselling/testing for affected persons with a mutation probability of ≥ 10%. Our objective was to evaluate the prevalence of the BRCA1/2 mutation(s) based on the checklist score (CLS).Methods A retrospective data analysis was performed on EOC patients with a primary diagnosis treated between 1/2011 – 5/2019 at the Central Essen Clinics, where a BRCA1/2 genetic analysis result and a CLS was available. Out of 545 cases with a BRCA1/2 result (cohort A), 453 cases additionally had an extended gene panel result (cohort B).Results A BRCA1/2 mutation was identified in 23.3% (127/545) in cohort A, pathogenic mutations in non-BRCA1/2 genes were revealed in a further 6.2% in cohort B. In cohort A, 23.3% (127/545) of patients had a BRCA1 (n = 92) or BRCA2 (n = 35) mutation. Singular EOC (CLS 2) was present in 40.9%. The prevalence for a BRCA1/2 mutation in cohort A was 10.8%, 17.2%, 25.0%, 35.1%, 51.4% and 66.7% for patients with CLS 2, 3, 4, 5, 6 and ≥ 7 respectively. The mutation prevalence in cohort B was 15.9%, 16.4%, 28.2%, 40.4%, 44.8% and 62.5% for patients with CLS 2, 3, 4, 5, 6 and ≥ 7 respectively.Conclusions The BRCA1/2 mutation prevalence in EOC patients positively correlates with a rising checklist score. Already with singular EOC, the prevalence of a BRCA1/2 mutation exceeds the required 10% threshold. Our data support the recommendation of the S3 guidelines Ovarian Cancer of offering genetic testing to all patients with EOC. Optimisation of the checklist with clear identification of the testing indication in this population should therefore be aimed for.HintergrundBRCA1/2-Mutationen sind die Hauptursache für erbliche epitheliale Ovarialkarzinome (EOC). Das Deutsche Konsortium für Familiären Brust- und Eierstockkrebs hat Einschlusskriterien definiert, welche als Checkliste abrufbar sind und Betroffenen mit einer Mutationswahrscheinlichkeit von ≥ 10% eine genetische Beratung/Testung ermöglichen. Unser Ziel war es, die Prävalenz der BRCA1/2-Mutation(en) auf Basis des Checklisten-Scores (CLS) zu evaluieren.Methoden Es erfolgte eine retrospektive Datenanalyse von EOC-Patientinnen mit Primärdiagnose, die zwischen 1/2011 – 5/2019 an den Kliniken Essen-Mitte behandelt wurden und für die ein BRCA1/2-Genanalyse-Ergebnis und ein CLS vorlag. Von 545 Fällen mit BRCA1/2-Ergebnis (Kohorte A) lag in 453 Fällen zusätzlich ein erweitertes Gen-Panel-Ergebnis (Kohorte B) vor.Ergebnisse In 23,3% (127/545) wurde in Kohorte A eine BRCA1/2-Mutation festgestellt, in Kohorte B zeigten sich bei weiteren 6,2% pathogene Mutationen in Nicht-BRCA1/2-Genen. In Kohorte A hatten 23,3% (127/545) der Patienten eine BRCA1- (n = 92) oder BRCA2- (n = 35) Mutation. Ein singuläres EOC (CLS 2) lag in 40,9% vor. Die Prävalenz für eine BRCA1/2-Mutation in Kohorte A betrug 10,8%, 17,2%, 25,0%, 35,1%, 51,4% und 66,7% für Patienten mit CLS 2, 3, 4, 5, 6 bzw. ≥ 7. Die Mutationsprävalenz in Kohorte B betrug 15,9%, 16,4%, 28,2%, 40,4%, 44,8% und 62,5% für Patienten mit CLS 2, 3, 4, 5, 6 bzw. ≥ 7.Schlussfolgerungen Die BRCA1/2-Mutationsprävalenz bei EOC-Patienten korreliert positiv mit steigendem Checklisten-Score. Bereits beim singulärem EOC überschreitet die Prävalenz einer BRCA1/2-Mutation die geforderte 10%-Schwelle. Unsere Daten unterstützen die Empfehlung der S3-Leitlinie Ovarialkarzinom, allen Patientinnen mit EOC eine genetische Testung anzubieten. Eine Optimierung der Checkliste mit eindeutiger Kennzeichnung der Testungsindikation in dieser Population ist daher anzustreben.
Keywords: ovarian cancer; BRCA mutation; hereditary breast and ovarian cancer; heritability checklist